Peran Ketua Yayasan dalam Meningkatkan Reputasi Lembaga melalui Media Sosial (Studi Kasus Di Pondok Pesantren Al qur’an Al falah 2 Nagreg Bandung) - Mukhdaji Albar; Dr. Ubaidillah (Journal of Innovative and Creativity, 2025)
This study aims to examine the role of a foundation chairperson in enhancing the reputation of the institution through the use of social media. The researcher seeks to understand how the chairperson of the Al-Qur'an Al- Falah 2 Nagreg Bandung Islamic Boarding School contributes to building a positive image of the institution and effectively expanding its public communication reach in the digital age. Social media has become one of the most influential communication tools for conveying messages, building trust, and creating connections with the wider community. However, not all institutions are able to utilize it optimally, especially in terms of strategic leadership representation. In this context, the chairperson plays a crucial role as the public face of the institution, capable of directing narratives, demonstrating transparency, and reinforcing the institution’s values and vision to society. Therefore, the chairperson’s active role in using social media in a planned and consistent manner is essential to enhancing the institution’s overall reputation.